Pengaruh Model Pembelajaran Treffinger Berbantuan Video Terhadap Hasil Belajar Peserta Didik - Finna Maulani; Gugum Gumilar; Iis Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to improve learning outcomes using the Treffinger learning model assisted by video. The research method used was a quasi-experiment with a nonequivalent control group design. The sample consisted of classes X-7 and X-12, selected using purposive sampling. Data were collected through essay-type learning outcome tests and analyzed using a t-test. The results showed a significant difference in learning outcomes between the group using the Treffinger model with video and the group using conventional learning. Therefore, the Treffinger learning model assisted by video has a positive effect on improving students’ learning outcomes.